The Problem of Memory and Oblivion: Bakhtin’s Mechanisms of Saving/Erasing Traces of Traditions in Cultural History - Irina L. Popova (Studia Litterarum)
The question of genre traditionally occupies a central position in Russian literary theory. This article focuses on the problem of memory and oblivion, their role in the development of literary genres, construction of images, and preservation and transmission of tradition. The concepts of great memory and deliberate oblivion in the cultural history were advanced by Mikhail Bakhtin in the materials he prepared for the revision of his book on François Rabelais in the early 1940’s. The overarching context for its study was informed by the theory of menippea. Menippea retrospectively established as a genre in the late 17th–18th centuries by critics who defined its generic characteristics and (re)invented its history from antiquity to the seventeenth century, gave a new impetus to Bakhtin’s genre theory, provided him with a perspective on the problem of generic identity and on the ways genres were constructed. Within the framework of menippea, he developed the following theories and concepts: the theory of “memory of the genre,” the theory of the “immanent memory” of literature as independent from the author’s individual memory, the concept of contactless transmission of tradition, and the concept of “great objective human memory” transcending linguistic, national, and cultural boundaries.